2022
DOI: 10.1177/07334648221109513
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Elder Abuse in the UK: A Description of Cases Reported to a National Helpline

Abstract: The abuse of older adults by someone in a position of trust—also known as elder abuse (EA)—has a severe impact on victims and society. However, knowledge about EA in the UK is limited in comparison to other types of interpersonal violence and international knowledge. The present study utilized secondary data from a UK national EA helpline to investigate the characteristics of reported cases. Over a one-year period between 2017 and 2018, 1,623 records met inclusion criteria. Descriptive statistics are provided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…This is supported by previous research which found that difficulties in managing finances is one of the earlier symptoms of dementia and assessment of financial capacity can identify people with MCI who are most likely to progress to dementia [ 25 , 26 ]. Financial abuse is the most prevalent form of elder abuse in the UK [ 27 ] and people with MCI or dementia are at greatest risk [ 28 ]. Fenton et al suggest that the early diagnosis of dementia can help identify those most at risk of financial exploitation, empower such individuals to avoid exploitation, and reduce the societal costs and consequences of exploitation [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by previous research which found that difficulties in managing finances is one of the earlier symptoms of dementia and assessment of financial capacity can identify people with MCI who are most likely to progress to dementia [ 25 , 26 ]. Financial abuse is the most prevalent form of elder abuse in the UK [ 27 ] and people with MCI or dementia are at greatest risk [ 28 ]. Fenton et al suggest that the early diagnosis of dementia can help identify those most at risk of financial exploitation, empower such individuals to avoid exploitation, and reduce the societal costs and consequences of exploitation [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…This could mean that both mistreatment and risk factors among people with dementia were underreported here. However, this under-reporting may be somewhat mitigated by the fact that one UK study found that 88% of mistreatment reports to a helpline are made by someone other than the victim ( Fraga Dominguez et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Author Title Year Study design/ level of evidence Li; Dong (12) Elder abuse and cognitive function among community-Dwelling older adults: Does abuse history matter? 2022 Cross-sectional V Ludvigsson et al (13) Experiences of elder abuse: a qualitative study among victims in Sweden 2022 Cross-sectional V Dominguez; Storey; Glorney (14) Characterizing Elder Abuse in the UK: A Description of Cases Reported to a National Helpline 2022 Cross-sectional V Weissberger et al (15) Elder abuse in the COVID-19 era based on calls to the National Center on Elder Abuse resource line 2022 Cross-sectional V Souza et al (16) Factors associated with the risk of violence against older adult women: a cross-sectional study 2021 Analytical IV Botngård et al (17) Elder abuse in Norwegian nursing homes: a cross-sectional exploratory study 2021 Analytical IV Alarcon et al (18) Percepção do idoso acerca da violência vivida 2020 Descriptive VI Meyer et al (19) Violence against older women: A systematic review of qualitative literature 2020 Qualitative systematic review V…”
Section: Chart 1-classification Of Articles Included In the Analysis ...mentioning
confidence: 99%